Binocular visual mechanisms in cortical areas I and II of the sheep. - Clarke, P G (1976)
1. Units were recorded in the primary and secondary visual areas (V1 and V2) of the sheep. They were stimulated binocularly, using an adjustable prism to vary the disparity. 2. Cells in V1 responded optimally to stimuli with very small or zero disparities, but cells in V2 frequently preferred disparities of several degrees crossed or uncrossed. Many cells in V2 were particularly selective to disparity, often giving no response to a monocular stimulus. 3. Cells preferring the same disparity occur in discrete columns, about 400 muM wide. Changes between columns result from a step displacement of the receptive field of one eye. The disparities encoded in successive columns seem to follow a regular sequence: crossed, zero, uncrossed, zero, etc. 4. In both V1 and V2, cells are clustered, perhaps in columns, according to their orientation preference and ocular dominance. In V2, the constant disparity columns appear to be independent of the orientation clusters.